Medical Care for Heart Diseases at the First Level of Care in Cuba - Niobis Cabrera Valdés; Yamilé Valdés González; Edilberto González Ortíz; Rubén Armas Molina; Laura Caridad Hurtado Gascón (Revista Finlay)
Foundation: heart disease is a common cause of morbidity, medical consultation, and hospitalization in the adult Cuban population. Heart disease, cerebrovascular disease, and diseases of the arteries, arterioles, and capillaries are among the top ten causes of death in the country, regardless of age.  Objective: to systematize the historical development of medical care for heart disease at the primary care level during the 21st century in Cuba.  Methods: documentary research was conducted using a qualitative method and exploratory scope. To identify the documents to be reviewed, searches were conducted in Scielo, Pubmed/Medline, and Google Scholar starting in 2000. The historical-logical method, document analysis, and systematization were used. 141 articles were studied, of which 39 were established as references.  Result: the development of medical care for heart disease at the primary care level during the 21st century in Cuba was periodized.  Conclusions: the historical development of primary care for heart disease was related to the social revolution, the political will of the State, and the ongoing improvement of the Cuban healthcare model in the 21st century, as part of the implementation of the Primary Health Care strategy.